INTEGRASI PEMBELAJARAN KONTEKSTUAL BERKEBUN UNTUK IMPLEMENTASI JOYFULL LEARNING DI SD - Insari, Indah Putri; Afridha Laily Alindra; Bunga Aldenina; Istiba Hikmatul Anwar; Kinanti Dilla Putri; Nurluthfi Azzahra; R Ulya Afifah; Renata Dwi Iswanti; Syaira Maulida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One innovative approach in education is the Joyful Learning method, which aims to create a fun and active learning atmosphere, so that students are more involved in the learning process. At SDN 5 Nagri Kaler, this method is implemented through the Tatanen di Bale Atikan (TdBA) program, an initiative of the Purwakarta District Education Office that integrates gardening activities into the school curriculum which also instills values of responsibility, discipline, and ecological awareness to students. This study aims to look at gardening activities as an implementation of joyful learning. The method used in this research is descriptive qualitative with data collection techniques through interviews, questionnaires, documentation, and literature review. The research subjects included teachers and fifth grade students of SDN 5 Nagri Kaler. The results showed that the application of the Joyful Learning method through the TdBA program increased students' enthusiasm and involvement in learning. Students showed a positive attitude towards gardening activities, which also contributed to their character development and practical skills. Thus, the integration of Joyful Learning method and TdBA program at SDN 5 Nagri Kaler is effective in creating a fun and meaningful learning environment, and supporting students' holistic development.